Space for Religion in Local Peacebuilding: The Role of the Church in Troubled Spaces (Impact: Journal of Transformation, 2024)
Many individuals and large communities in the world lack the will and the ability for truepeacebuilding. Truly born-again Christians are best endowed and mandated to be effectivepeacebuilders, starting from their respective local spaces. Although it is true that Jesushimself was born and lived all his earthly life in a very troubled and peaceless space and dieda very violent death, it had been prophesied that, among his other real identities and offices,he would come as the Prince of Peace. Although in his radical teaching he said he did notcome to bring peace but a sword, he himself was the most peaceful human being and the mosteffective peacemaker. He also sent his disciples to violent communities as peacefulemissaries. Before his death, resurrection, and ascension to heaven he gave his special divinepeace to his disciples (the first church). Sin is the cause and breeding ground for hatred,conflict, and lack of peace. True salvation in Jesus Christ is the only remedy for sin and thesource of power for true love, true personal peace, and genuine peacebuilding. When a personis made righteous through our Lord, Jesus Christ, he or she acquires peace with God. Aperson who is genuinely justified is able to love genuinely, deliberately abhor wickedness,and decisively live peaceably with all people, thus being a pragmatic peacebuilder. Myresearch method for the paper is historical-grammatical exegesis. Through it, I seek todiscover the meaning of peace and peacebuilding in various Bible texts as was intended bythe authors to be understood and applied by the original hearers  Theological application and recommendations for peacebuilding are proposed for the churchin the African setting based on specific Bible texts for specific needs.